Preparation and characterization of sulfonated graphene-enhanced poly (vinyl alcohol) composite hydrogel and its application as dye absorbent. (9th March 2015) - Li, Hong; Fan, Jinchen; Shi, Zixing; Lian, Min; Tian, Ming; Yin, Jie
Abstract: In this paper, sulfonated graphene (SG) were incorporated into the poly (vinyl alcohol) (PVA) networks to fabricate the SG/PVA (SP) composite hydrogel. The as-prepared SP hydrogel exhibited enhanced mechanical property with a small amount of SG into the PVA matrix. In the meantime, the SP hydrogel showed specific adsorption of cationic dyes, such as Methylene Blue (MB), Malachite Green (MG). Studies on the adsorption isotherm and kinetics of the SP hydrogel showed that the equilibrium and kinetic adsorptions could be well depicted based on Langmuir isotherm and pseudo-second-order kinetics model, respectively. Due to the π-π conjugated structure and sulfonic acids on the SG surface, pH and ionic strength had less impact on the adsorption ability of SP hydrogel toward MB. Furthermore, it was also found that the SP hydrogel could be used as intelligent absorbent in selective adsorption and separation of the dye mixtures. Graphical abstract: